Non-genetic adaptive resistance to KRASG12C inhibition: EMT is not the only culprit - Ning, Wenjuan; Marti, Thomas M.; Dorn, Patrick; Peng, Ren-Wang (Frontiers in Oncology, 2022)
Adaptions to therapeutic pressures exerted on cancer cells enable malignant progression of the tumor, culminating in escape from programmed cell death and development of resistant diseases. A common form of cancer adaptation is non-genetic alterations that exploit mechanisms already present in cancer cells and do not require genetic modifications that can also lead to resistance mechanisms. Epithelial-to-mesenchymal transition (EMT) is one of the most prevalent mechanisms of adaptive drug resistance and resulting cancer treatment failure, driven by epigenetic reprogramming and EMT-specific transcription factors. A recent breakthrough in cancer treatment is the development of KRASG12C inhibitors, which herald a new era of therapy by knocking out a unique substitution of an oncogenic driver. However, these highly selective agents targeting KRASG12C, such as FDA-approved sotorasib (AMG510) and adagrasib (MRTX849), inevitably encounter multiple mechanisms of drug resistance. In addition to EMT, cancer cells can hijack or rewire the sophisticated signaling networks that physiologically control cell proliferation, growth, and differentiation to promote malignant cancer cell phenotypes, suggesting that inhibition of multiple interconnected signaling pathways may be required to block tumor progression on KRASG12C inhibitor therapy. Furthermore, the tumor microenvironment (TME) of cancer cells, such as tumor-infiltrating lymphocytes (TILs), contribute significantly to immune escape and tumor progression, suggesting a therapeutic approach that targets not only cancer cells but also the TME. Deciphering and targeting cancer adaptions promises mechanistic insights into tumor pathobiology and improved clinical management of KRASG12C-mutant cancer. This review presents recent advances in non-genetic adaptations leading to resistance to KRASG12C inhibitors, with a focus on oncogenic pathway rewiring, TME, and EMT.